Employing artificial intelligence techniques to make films - Aya Khalid Naji (الاكاديمي)
The film business is one of the many industries that artificial intelligence is inexorably involved in due to the rapid advancement of technology. Artificial intelligence benefits the industry at every stage of the production cycle. This paper focuses on five phases: script writing in AI, picture generation in AI, voice recordings in AI, make animation in AI, movie editing, with a presentation of artificial intelligence tools.